Implementing the element of Islamic perspective view in mental health problems - Hanif, Md Lateh @ Junid; Zaizul, Ab Rahman; Ahmad Yunus, Mohd Noor (IAEME Publication, 2019)
Scholars emphasized that the practice of the riya’will be punished and even the nature riya’itself will bring the anger and torment of Allah S.W.T. The nature of riya depends on the quality, purity, and sincerity of the intentions. It compromised of three categories. If the driver of the practice coincides with his motivator, so both become equally strong, then both should be dropped and the practice is considered to be neither sympathy nor innocent. If the impetus of riya 'is stronger and prevents others, the practice will not benefit, but will give harm and torture. Torture in such a state is lighter than the practice of torture simply because of riya '. If the intent to draw closer to Allah is heavier or more likely to be compared to other impulses, then one will be rewarded just as the excess of the strength of his sincerity, as the word of Allah s.w.t: So whoever does an atom's weight of good will see it. (Al-Zalzalah 99: 7-8)